The Consistency of Basic Principles of Internal Audit at Private Enterprises - L. NOVICHENKO; О. V. SHCHYRSKA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
Economic challenges of our time determine the need in clear identification and specification of management functions as part of the business processes and their control. European practices of business development give evidence of the need in a comprehensive approach to organizational, methodological and practical actions focused on building up the internal control system in symbiosis with the management department. The research objective involved an analysis of the consistency of basic principles underlying the quality of internal control at private enterprises through outlining the functions, methods and procedures of internal audit.   The purposes of international audit (verification of financial statements, compliance control, operational audit) are outlined. The goal and assignments of internal audit are determined in the context of private business demands. A revised approach to defining the set of functions of international audit in view of the demands articulated by business enterprises operating in the conditions of crisis economy is proposed. The essential meaning of the categories of “method”, “technique” and “methodology” is highlighted in the context of internal control.      The conclusion is made that the assignments of internal audit need to be solved by use of creative methods of control and innovative approaches to various situations, which requires a multifaceted classification of internal audit in view of its customer demands: technical audit, technological audit, organizational audit, legal audit, environmental audit, social audit, marketing audit. An information platform for balanced decision-making involves combinations of control functions and entails the emergence of unified forms of internal audit: risk-oriented audit, business-oriented audit, factor-oriented audit, etc.